Histological response assessment following neoadjuvant isolated limb perfusion in patients with primary, localised, high-grade soft tissue sarcoma. (17th February 2016) - Andreou, Dimosthenis; Werner, Mathias; Pink, Daniel; Traub, Frank; Schuler, Markus K.; Gosheger, Georg; Jobke, Björn; Reichardt, Peter; Tunn, Per-Ulf
Abstract: Purpose : Histological response assessment following neoadjuvant treatment can help identify patients at a higher risk for systemic disease progression. Our goal was to evaluate whether mitotic count and the amount of viable tumour following neoadjuvant isolated limb perfusion (ILP) for primary, locally advanced, non-metastatic, high-grade extremity soft tissue sarcoma correlate with prognosis. Patients and methods : This study is a retrospective analysis of 61 patients who underwent neoadjuvant ILP followed by surgical resection with curative intent between 2001 and 2011. Non-parametric analyses were carried out with the Mann-Whitney U and the Wilcoxon signed-rank test. Survival curves were calculated with the Kaplan-Meier method and compared with the log-rank test. Results : The median follow-up was 44 months for all patients and 55 months for survivors. The amount of viable tumour after ILP had no correlation with overall (OS) ( P = 0.227) or event-free (EFS) ( P = 0.238) survival probability. Patients with a low mitotic count after ILP had a significantly higher OS ( P < 0.001), EFS ( P = 0.002) and post-relapse survival probability ( P = 0.030) compared to patients with an intermediate or high mitotic count. Conclusions : The mitotic count following ILP for primary, high-grade, locally advanced, non-metastatic soft tissue sarcoma appears to significantly correlate with prognosis. If these results are validated in a prospective setting, they could provide a rationale for the design of adjuvant systemic chemotherapy trials with the goal of improving the prognosis of patients with an intermediate or high mitotic count after ILP.